(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: Ecotourism focuses on the protection of flora and fauna, environmental management, poverty reduction, and economic enhancement. Many developing countries utilize it to integrate socioeconomic development with biodiversity conservation, promoting sustainable development. Due to lockdowns and travel restrictions brought on by the COVID-19 pandemic during 2020-2021, tourism was severely affected. Purpose: This study examines the effects of the global pandemic on tourist visitation and socioeconomy at the community level in Sikles village of the Annapurna Conservation Area. Design/methodology/approach: Eighty questionnaire surveys, two focus group discussions, and five key informants’ interviews were conducted to collect primary data, along with secondary data on international tourist flow and revenue generated in Sikles. A 5-point Likert scale was used to assess the spillover impacts of the pandemic on different socioeconomic facets of the local community. Findings: The result of the paired sample t-test shows no significant difference in the average annual income of the people involved in tourism before and during the pandemic in fiscal years 2075/76 and 2076/77 at p > 0.05, despite the pandemic. Unlike most cases, the income from tourism has not changed significantly, even during the pandemic in Sikles. This is because the locals took advantage of the lockdown to promote ecotourism destinations like Hugu, Kori, and Kaphuche on digital platforms, which in turn increased the domestic tourism flow in Sikles. However, there was a significant loss in the revenue collection by ACAP from international tourists. Conclusion: The study concludes that, despite global tourism declines during the COVID-19 pandemic, Sikles maintained a stable tourism income due to strong local promotion of ecotourism sites, which boosted domestic visitation. However, ACAP faced significant revenue losses due to reduced international tourism, underscoring the need for diversified and resilient tourism and conservation strategies. Keywords: Ecotourism, COVID-19 pandemic, rural destination, ACAP, crisis, livelihood, socioeconomy